Leaching Characteristics and Mechanisms of Fluorine and Phosphorus from Phosphogypsum - Wanqiang Dong; Xiangyi Deng; Liqi Chai; Yuefei Zhang; Haodong Chen; Hanjun Wu; Ru’an Chi (Molecules)
As a large-volume industrial solid waste generated during the production of wet-process phosphoric acid, the primary disposal method for phosphogypsum (PG) currently involves centralized stockpiling, which requires substantial land use. Additionally, PG contains impurities, such as phosphorus, fluorine, and alkali metals, that may pose potential pollution risks to the surrounding environment. However, the mechanisms governing the co-release of phosphorus and fluorine impurities alongside valuable metal cations during leaching remain unclear, posing challenges to efficient disposal and utilization. This study compares the leaching characteristics of cations and anions in PG of different particle sizes through static pH leaching experiments. Using Visual MINTEQ simulation combined with XRD, XPS, and FT-IR characterization methods, we analyzed the leaching mechanisms and key controlling factors for various metal elements and inorganic elements, like phosphorus and fluorine, under different pH conditions. The experimental results show that Ca, Al, Fe, Ti, Ba, Sr, Y, and PO43− in PG are more easily released under acidic conditions, while Si, Zn, Co, and F are primarily influenced by the content of soluble components. The dynamic “dissolution–crystallization” reaction of CaSO4·H2O significantly impacts the leaching of fluorine, and the XRD, XPS, and FT-IR characterization results confirm the presence of this reaction during the leaching process. This research provides theoretical guidance for the environmental risk assessment of stockpiled PG and the recovery of phosphorus, fluorine, and valuable metal resources from PG.